Ecotourism Development Strategy of Kembang Kuning Tourism Village Based on the 3S Concept in East Lombok - Hasnia Minanda; Baiq Nikmatul Ulya; Siti Anggriana; Nur Afiah; Lalu Ferdi Ferdiansyah (Faculty of Economics and Business, University of Mataram, 2025)
This study aims to analyze the ecotourism potential of Kembang Kuning Tourism Village in East Lombok through the concept of Something to See, Something to Do, and Something to Buy (3S). The research adopts a descriptive qualitative approach based on field observations, interviews, and literature studies. The findings show that the village possesses significant potential to develop as a sustainable community-based tourism destination. The aspect of Something to See includes the scenic beauty of the Rinjani foothills, waterfalls, and traditional cultural landscapes that enhance the visual appeal of the destination. Something to Do reflects a variety of participatory and educational activities, such as trekking, agricultural tourism, and cultural workshops, that engage visitors with local life. Meanwhile, Something to Buy highlights local creative economy products such as coffee, honey, and handicrafts, representing economic empowerment for local residents. Overall, the integration of natural, cultural, and economic attractions, supported by government programs and digital promotion, strengthens Kembang Kuning’s position as a leading sustainable ecotourism village. The study concludes that participatory management and environmental preservation are key strategies to ensure the long-term competitiveness and sustainability of the destination